2019
DOI: 10.1177/0004867419848035
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of structural neuroimaging in first-episode psychosis: A systematic review

Abstract: Background: Australian and US guidelines recommend routine brain imaging, either computed tomography or magnetic resonance imaging, to exclude structural lesions in presentations for first-episode psychosis. The aim of this review was to examine the evidence for the appropriateness and clinical utility of this recommendation by assessing the frequency of abnormal radiological findings in computed tomography and magnetic resonance imaging scans among patients with first-episode psychosis. Methods: PubMed and Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…In this case, the temporality between the improvement of psychotic symptoms and treatment of MS would suggest an association. Furthermore, it is likely that what were presumed to be negative symptoms, were more likely symptoms of fatigue and lethargy that are common in MS. Less than 1% of neuroimaging in first episode of psychosis yields clinical significance, and therefore, neuroimaging should only be performed when clinically indicated (Forbes et al, 2019). We propose that neuroimaging could be considered in the presence of apparent persistent negative symptoms in a young person, as MS is a rare but important differential diagnosis of first presentation of psychosis.…”
Section: To the Editormentioning
confidence: 99%
“…In this case, the temporality between the improvement of psychotic symptoms and treatment of MS would suggest an association. Furthermore, it is likely that what were presumed to be negative symptoms, were more likely symptoms of fatigue and lethargy that are common in MS. Less than 1% of neuroimaging in first episode of psychosis yields clinical significance, and therefore, neuroimaging should only be performed when clinically indicated (Forbes et al, 2019). We propose that neuroimaging could be considered in the presence of apparent persistent negative symptoms in a young person, as MS is a rare but important differential diagnosis of first presentation of psychosis.…”
Section: To the Editormentioning
confidence: 99%
“…It is potentially useful to establish a baseline study in FEP, as schizophrenia has been shown to reduce cortical volume and increase ventricular size over time (Olabi et al, 2011). A recent systematic review concluded that routine brain imaging could not be recommended due to low yield and that history, neurological examination and mental status should be used to determine the likelihood of structural lesions to guide decisions about imaging (Forbes et al, 2019). The most recent NICE and Canadian guidelines specifically recommend against routine screening due to low yield and lack of cost-effectiveness (Addington et al, 2017;National Institute for Health and Care Excellence, 2008;Pringsheim et al, 2017).…”
Section: Relevancementioning
confidence: 99%
“…Additional factors that may influence imaging usage include ambiguous and contradictory international clinical practice guidelines and the fear of missing a potentially treatable cause of psychosis or serious neurological illness, which may result in patient harm and medicolegal risk. 2 The RANZCP guidelines currently include MRI as part of the workup for first-episode psychosis, with a caveat that disagreement exists around this recommendation. 3…”
Section: Neuroimaging For First-episode Psychosismentioning
confidence: 99%
“…3 Evidence A systematic review of 16 studies, which included 2312 individual patients, looked at the clinical utility of brain imaging with CT or MRI in first-episode psychosis and found that structural abnormalities were a possible cause of psychotic symptoms in just 0.4% of patients. 2 A further Australian study of 805 patients under the age of 50 without neurological signs over a 7-year period found the diagnostic yield of CT in the setting of psychosis to be very low. 4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation